Adaptation of ISO/IEC 15504 standard to SMBs needs - Pasini, Ariel (2011)
An analysis is presented on the possibility of deploying the ISO/IEC 15504 standard in the various SMBs categories defined by the European Union, in particular, on the roles that would be necessary for a company and the roles that each of the SMBs categories can support. Scenarios are provided, defining a set of roles for each category, and the possibility is analyzed of meeting Work Product requirements that are part of the Engineering and Project processes, as well as the attributes of capacity levels 2 and 3.